Abnormal cytokine profiles in patients with idiopathic dilated cardiomyopathy and their asymptomatic relatives. Issue 3 (March 1996) - Marriott, J. B.; Goldman, J. H.; Keeling, P. J.; Baig, M. K.; Dalgleish, A. G.; McKenna, W. J.
Abstract : OBJECTIVES: Immunological abnormalities in idiopathic dilated cardiomyopathy (DCM) include an increase in soluble interleukin (IL)-2 receptor, disease specific cardiac autoantibodies, an HLA-DR4 association, and familial aggregation of disease; however, cytokine profiles have not been defined. Serum concentrations of IL-2, IL-4, IL-10, and IL-12 were measured in patients with DCM (WHO criteria), relatives with asymptomatic left ventricular enlargement (LVE), patients with ischaemic heart failure (IHD), and healthy controls. DESIGN: Serum from 20 individuals from each of the four groups was assayed for cytokine concentrations by a commercial enzyme linked immunosorbent assay. RESULTS: IL-2 concentrations were abnormally increased in DCM patients and relatives with LVE. Concentrations of IL-10 were increased in DCM patients. Concentrations of IL-4 and IL-12 were not increased in any of the groups. CONCLUSION: These abnormalities may reflect defective/inappropriate T cell function in patients with DCM and in their relatives with LVE.